OPTIMASI PRODUKSI PADA INDUSTRI KECIL DAN MENENGAH KARYA UNISI DENGAN PENERAPAN MODEL LINEAR PROGRAMMING - Y. Rahmat Akbar; Mar’aini Mar’aini (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the obstacles faced by the company in obtaining maximum profit and to determine the right combination of products so that the company obtains maximum profit. This research was conducted on small and medium industries (IKM) of Karya Unisi in Tampan District, Pekanbaru City, Riau Province, Indonesia. The research design uses quantitative data with an applied research design. The analytical method used in this research is through a Linear Programming approach. The data was processed using software POM-QM for Windows V5.2. The results showed that the obstacles faced by the company were the limitations of raw materials and labor hours. From the results of calculations and data processing, it is found that to produce maximum profit with existing constraints and limitations, the optimal number of production that can be done by the company is 30 doors and 70 windows every month. By producing this amount, the company will get a maximum profit of Rp.10.200.000, - with the assumption that the profit is based on the objective function and the existing constraints.